2016
DOI: 10.1126/science.aag3145
|View full text |Cite
|
Sign up to set email alerts
|

Depleting dietary valine permits nonmyeloablative mouse hematopoietic stem cell transplantation

Abstract: A specialized bone marrow microenvironment (niche) regulates hematopoietic stem cell (HSC) self-renewal and commitment. For successful donor-HSC engraftment, the niche must be emptied via myeloablative irradiation or chemotherapy. However, myeloablation can cause severe complications and even mortality. Here we report that the essential amino acid valine is indispensable for the proliferation and maintenance of HSCs. Both mouse and human HSCs failed to proliferate when cultured in valine-depleted conditions. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
128
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(134 citation statements)
references
References 17 publications
3
128
1
2
Order By: Relevance
“…Dietary restriction of valine results in a relatively selective depletion of HSCs from BM. As a result, transplanted HSCs can effectively engraft in valine-restricted recipient mice under non-myeloablative conditions [50]. Although the molecular basis for these activities remains unclear, they suggest that dietary valine directly regulates HSC maintenance in the BM niche.…”
Section: Amino Acid-dependence Of Hscs and Leukemic Cellsmentioning
confidence: 97%
See 1 more Smart Citation
“…Dietary restriction of valine results in a relatively selective depletion of HSCs from BM. As a result, transplanted HSCs can effectively engraft in valine-restricted recipient mice under non-myeloablative conditions [50]. Although the molecular basis for these activities remains unclear, they suggest that dietary valine directly regulates HSC maintenance in the BM niche.…”
Section: Amino Acid-dependence Of Hscs and Leukemic Cellsmentioning
confidence: 97%
“…AAs than does peripheral blood [50]. Among them, valine is required for HSC proliferation in vitro and for repopulation capacity following transplantation in vivo.…”
Section: Amino Acid-dependence Of Hscs and Leukemic Cellsmentioning
confidence: 99%
“…Furthermore, the indirect effect on hematopoietic cells of the hematopoietic microenvironment may be a critical factor reported then and still of relevance now in understanding marrow committed stem cells (8,(16)(17). Finally, the lack of use of a clonal Friend virus in prior studies (3,4,8,(16)(17) may have introduced confounding variables, not testable in the present studies.…”
Section: And P-erk But Increased Levels Of Expression Of P-s6k P-jnkmentioning
confidence: 59%
“…The longevity of Friend virus-infected marrow in LTBMCs from C57BL/6 mice may have reflected the in vitro culture system in which high levels of added 17-hydroxy corticosteroid and absence of immunoregulatory cells represent artificial growth conditions for bone marrow (3)(4)(5)(6)(7)(8). Furthermore, the indirect effect on hematopoietic cells of the hematopoietic microenvironment may be a critical factor reported then and still of relevance now in understanding marrow committed stem cells (8,(16)(17). Finally, the lack of use of a clonal Friend virus in prior studies (3,4,8,(16)(17) may have introduced confounding variables, not testable in the present studies.…”
Section: And P-erk But Increased Levels Of Expression Of P-s6k P-jnkmentioning
confidence: 99%
“…3 The Nakauchi laboratory showed that a diet deficient in the essential amino acid valine, resulted in the selective depletion of HSCs in the bone marrow of mice, which allowed for a successful transplant of HSCs without an additional preconditioning regimen. 4 Ultimately, it has also been reported that multiple cycles of short-term fasting, and the accompanying restricted uptake of vitamins and essential amino acids, leads to signal transduction changes in HSCs and niche cells which promote stress resistance, self-renewal, and regeneration. 5 We can now add to this list a novel yin/yang role of folate in hematopoiesis.…”
mentioning
confidence: 99%